Comparison of Epiphyte Diversity Between Forest Trees and Oil Palm Within the Forest-Oil Palm Plantation Boundary in SALCRA Plantation Areas, Bau, Sarawak - Bridgette, Philip (UNIMAS, 2024)
Epiphytes depend on other plants or trees for physical support, nutrients, or light, and they are critical indicators of a healthy forest as they are sensitive to environmental changes. This study is conducted with the objectives of i) to determine the epiphyte species composition in oil palm and forest plots, ii) to compare and frequency of individual species and the diversity of epiphytes based on the age of forests and oil palms as well as the distance of oil palm sample plots and forest sample plots from the forest-oil palm common boundary respectively, and iii) to establish the relationship between the epiphyte species frequency and diversity in the oil palm and forest sample plots. This study was conducted in Bau district, mainly in the Jagoi area. A total of 17 forest plots and 17 oil palm plantation plots were sampled. The frequency of individual species of epiphytes and overall plot diversity are assessed based on two factors: the distance of the plots to the forest-oil palm boundary (10 m and 100 m) and age class. Three forest ages, i.e., i) < 25 years, ii) 25-40 years, and iii) > 40 years, and three age classes of oil palm were identified, i.e., i) < 5 years, ii) 5-10 years, and iii) > 15 years). A sample plot of 10 m x 10 m in the forest was established, and trees with DBH ≥ 5 cm and height ≥ 2m from the forest floor were enumerated. Five individual oil palms at 10 m and 100 m distances from the forest-oil palm boundary were also enumerated. The number of epiphytes in all measured trees and oil palms were identified and counted. The abundance and diversity of epiphytes were calculated using the Shannon-Wiener diversity index and compared between different habitats. According to the findings, there is a significant difference between the number of species and the total count of epiphytes as a function of the age of the forest and oil palm. The number of species and the total count of epiphytes are not significantly affected by the distance of the plots from the forest-oil palm common boundary. The results also show that several epiphyte species abundance correlates with the age of the oil palms and the forest, whereas there is little to no correlation between the frequency of abundance of epiphytes species and the distance of the plots from the forest-oil palm boundary. The study concludes that the forest and oil palm ages influenced epiphytes' diversity and abundance. Meanwhile, the distance to the forest-oil palm boundary is not a significant determinant of species abundance of the epiphytes.